Effects of two deproteinizing methods on shear bond strength of orthodonic metal brackets bonded to demineralized teeth an in-vitro study - Zakerinejad, Maryamnahal
The aim of the study is to evaluate the effectiveness of the deproteinization of the enamel surface in the shear bond strength of orthodontic metal brackets bonded to demineralized teeth. Transbond XT (light-cured adhesive) and System 1+ (chemically-cured adhesive) were used for direct bonding of integral Dyna-Lock stainless steel brackets. 5.2% Sodium hypochlorite and 10% papaya latex gel were employed to enamel surface as deproteinizing agent. Fifty four lower bovine incisors were embedded in resin blocks and demineralized using Buskes' protocol (5 days, 37°C ). Samples were randomly allocated to six groups: 1) Transbond XT; 2) System 1+; 3) Transbond XT deproteinized with sodium hypochlorite; 4) System 1+ deproteinized with sodium hypochlorite; 5) Transbond XT deproteinized with papaya latex gel; 6) System 1+ deproteinized with papaya latex gel. The mechanical tests were performed in a Shimatzu testing machine 24 hours after bonding brackets. Data were analyzed with a one way analysis of variance (ANOVA) and t-test with a Bonferoni test for multiple comparisons (P-value<0.05) Bonding failure site was recorded under microscope and analyzed by Fisher exact test.